The Role of AI-Driven Project Management in Software Development: Trends, Benefits, and Challenges - Mood, Sanjay (International Journal of Computer Sciences and Engineering, 2024)
In today’s fast-evolving software industry, the demand for efficient, adaptive, and intelligent project management solutions has never been greater. Artificial intelligence (AI) is emerging as a transformative force, revolutionizing how teams operate by automating routine tasks, offering predictive insights, and enabling data-driven decision-making. These tools empower project managers to anticipate challenges, streamline resources, and optimize workflows, resulting in more efficient project execution. By reducing the time spent on administrative tasks like scheduling and reporting, AI allows managers to focus on strategic objectives, fostering innovation and team collaboration. This paper explores the latest advancements in AI-powered project management, including predictive analytics, task automation, and tools for enhancing collaboration in remote environments. It highlights real-world applications, such as improving project delivery speed, enhancing scalability, and mitigating risks, while also addressing challenges like system integration, data privacy, and skill gaps. Through industry case studies and examples, this study offers actionable strategies for adopting AI in project management and outlines its potential to reshape the future of software development. By bridging the gap between human expertise and machine intelligence, AI promises to redefine project management as an indispensable asset for success in an increasingly competitive landscape.